Establishment of Integrated Non-Communicable Disease Development Post (Posbindu PTM) in Muhammadiyah Branch Leadership (PCM) Area, Mangkubumi District, Tasikmalaya City - Hana Ariyani; Ida Rosidawati; Novita Ramadanty; Lusi Bilqis Amelisqi; Yevi Tri Khotami Rahmawati; Inun Nurilah; Muhammad Rofiq Najib; Adi Rifan Juanda (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Non-Communicable Diseases (NCDs) are still a global problem that causes death every year. One of the efforts to prevent and control NCDs is by establishing Integrated Non-Communicable Disease Development Post (Posbindu PTM). The purpose of this activity is to initiate the formation of Posbindu PTM in the area of the Muhammadiyah Branch Manager/Pimpinan Cabang Muhammadiyah (PCM) Mangkubumi District, Tasikmalaya City. The strategies used are recruitment, outreach, formation, training of cadres and simulations of Posbindu PTM implementation. The method of implementing the activity is through participatory community empowerment, the Participatory Rural Appraisal model in collaboration with PKM Sambongpari, PCM and PCA, Mangkubumi District, Tasikmalaya City. This activity was attended by 10 cadres from members of the Aisyiyah Branch Manager/Pimpinan Cabang Muhammadiyah (PCA), Mangkubumi District, Tasikmalaya City. While the Posbindu participants came from the PCM and PCA monthly recitation congregation of Mangkubumi District, totaling 48 people. The evaluation results showed that knowledge about Posbindu, skills in using medical devices, and interview skills of all cadres increased. Likewise, the participants said that this Posbindu activity could make it easier for residents to access free health check services. The conclusion from this activity is that the formation of Posbindu PTM can increase the knowledge and skills of cadres and increase the accessibility of Muhammadiyah members in having their health checked.